A stranger's game - Johnston, Joan, 1948- (Johnston, Joan, 1948- Bitter Creek series., 2008)
FBI Special Agent Breed Grayhawk has the hottest sex in his life with a stranger who calls herself Grace Smith, only to discover early the next morning that her real name is Merle Raye Finkel -- and she's a convicted double murderer who broke her parole a year ago and disappeared. Now she's his prime suspect in a terrorist threat against the U.S. president. With just five days until the president arrives in Austin, Texas, the last thing the FBI needs is a serial killer on the prowl...and a terrorist suspect who will stop at nothing to clear her name. The clock is ticking down, and Agent Grayhawk is racing time to discover the truth about his dangerous lover--From publisher description.